2016
DOI: 10.1139/cjss-2015-0083
|View full text |Cite
|
Sign up to set email alerts
|

Response of Manitoba soils to banding phosphorus with sulfate or carbonate salts

Abstract: Applications of sulfate and carbonate salts have been shown to improve the solubility of phosphorus (P) in model calcareous soils. It is unclear how these treatments will influence P solubility in real soils. The objective of this study was to determine the effect of sulfate or carbonate salts on P solubility in selected Manitoba soils. We hypothesized that the application of carbonate or sulfate salts in a fertilizer band could enhance the solubility of P in Manitoba soils. Different salt mixtures were prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…It can be shown that all three types of salt additions could increase the P adsorption in the soil solution to compare with the control sample. However, P adsorption can be varied according to the type of salts (Mihiri et al 2016). After addition of 0.01M of all salts, it has been occur an increase of measured P adsorption which reached 2.6%, 4.31%, and 8.39% in the case of P-KCl, P-NaCl and P-CaCl 2 , respectively.…”
Section: Salt Effect On P Adsorptionmentioning
confidence: 99%
“…It can be shown that all three types of salt additions could increase the P adsorption in the soil solution to compare with the control sample. However, P adsorption can be varied according to the type of salts (Mihiri et al 2016). After addition of 0.01M of all salts, it has been occur an increase of measured P adsorption which reached 2.6%, 4.31%, and 8.39% in the case of P-KCl, P-NaCl and P-CaCl 2 , respectively.…”
Section: Salt Effect On P Adsorptionmentioning
confidence: 99%
“…이상으로 높은 토양에서는 토양산도에 미치는 효과가 미미하거나(Manimel Wadu et al, 2016) 오히려 pH가 감소하는 경우도 보고되었다(Lee and Hong, 2016). 모든 처리구의 토양 EC는 0.19 -0.21 dS m -1 , 유기물 함량은 16 -17 g kg -1 , 유효인산 함량은 262 -291 mg kg -1 , 치환성 칼륨 함량은 0.22 -0.26 cmol c kg -1 , 치환성 칼슘 함량은 8.0 -8.6 cmol c kg -1 , 치환성 마그네슘 함량은 2.6 -2.7 cmol c kg -1 로서 유의적인 차이가 없었다.고구마 생육 및 수량 수확기 고구마 생육과 수량은Table 2와 같다.…”
unclassified